2009
DOI: 10.1021/jp810324v
|View full text |Cite
|
Sign up to set email alerts
|

FRET Quenching of Photosensitizer Singlet Oxygen Generation

Abstract: The development of activatable photodynamic therapy (PDT) has demonstrated a utility for effective photosensitizer quenchers. However, little is known quantitatively about Forster resonance energy transfer (FRET) quenching of photosensitizers, even though these quenchers are versatile and readily available. To characterize FRET deactivation of singlet oxygen generation, we attached various quenchers to the photosensitizer pyropheophorbide-alpha (Pyro) using a lysine linker. The linker did not induce major chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
104
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 129 publications
(109 citation statements)
references
References 42 publications
5
104
0
Order By: Relevance
“…The light irradiation causes the photosensitizer to generate cytotoxic singlet oxygen that destroys tumor cells through apoptosis or necrosis [6]. In addition, the selective accumulation of photosensitizers like protoporphyrin IX (PpIX) in tumor tissues provides an intense fluorescence signal that also can be employed in photodynamic imaging (PDI) [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The light irradiation causes the photosensitizer to generate cytotoxic singlet oxygen that destroys tumor cells through apoptosis or necrosis [6]. In addition, the selective accumulation of photosensitizers like protoporphyrin IX (PpIX) in tumor tissues provides an intense fluorescence signal that also can be employed in photodynamic imaging (PDI) [7].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that various photosensitizer-encapsulated nano-sized carriers could enhance the tumor target specificity and therapeutic efficacy in cancer treatment, compared to free photosensitizer [2,3,11]. On the other hand, there are some efforts to control the photosensitizer's activity using quenching/dequenching system, which show the specific recovery of the photosensitizer's activity in target tumor tissue [7]. For this purpose, the quenched nano-sized drug carriers have been developed to recover the quenched photosensitizer's activity under tumor-specific stimuli such as tumoral acidic pH or tumor-specific enzymes [12,13], whereas the carriers at normal state presented the 'off' state with no fluorescence signal and phototoxicity with light exposure, due to the quenching effect.…”
Section: Introductionmentioning
confidence: 99%
“…Porphyrin fl uorescence self-quenching has been shown to be highly correlated with self-quenching of singlet oxygen quantum yield. [ 16 ] Although less quenched, 1% porphyrin-lipid GPVs generated substantially more fl uorescence and thus more singlet oxygen (hundreds of fold more, based on the quenching in porphysomes of similar composition [ 10 ] ), they did not form pores in response to laser irradiation, indicating that pore formation is not a result of singlet oxygen interaction with the membrane. This is consistent with previous examination of singlet oxygen generation of porphyrins anchored in low molar percentages (1-10%) in phospholipid giant unilamellar vesicles, which did not produce visible membrane poration in response to irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…Protoporphyrin IX (PpIX) is another photo-sensitizer that its accumulation in tumor tissues provides an intense fluorescence signal that also can be employed in photodynamic imaging (PDI) [102]. Lee et al designed the PpIX-conjugated GC nanoparticles (PpIXeGCe NPs) based on cellular on/off system for synchronous photodynamic imaging (PDI) and PDT in cancer treatment [97].…”
Section: Photo-sensitive Chitosan Nanocarriersmentioning
confidence: 99%